Marine Sponge-Derived Fungi: Fermentation and Cytotoxic Activity - Putu Oka Samirana&, Yosi Bayu Murti, Riris Istighfari Jenie, Erna Prawita Setyowati (Journal of Applied Pharmaceutical Science, 2021)
Bioactive compounds from sponges are produced under the influence of several factors including enzymes, nutrients, and the result of symbiosis with other microbes like fungi. Marine sponge-derived fungi are a potential source producing new bioactive compounds for future cancer therapies. In this review, we summarize 132 components consisting of 16 extracts, 5 fractions, and 111 isolates obtained from 30 genera of marine sponge-derived fungi tested on 317 types of cell line cancers from articles published through June 2020. These components were classified as very strong, strong, and moderate cytotoxic activity based on their IC50, respectively, and 56 components of marine sponge-derived fungi were reported as very strong cytotoxic activity. Components that have very strong cytotoxic activity have been summarized, including polyketide derivatives, lipopeptides, cyclodepsipeptides, decalin derivatives, xanthone derivatives, phenol derivatives, cytochalasins, peptaibiotics, phthalides, anthraquinones, terpenes, decalin derivatives, and lactones. In producing bioactive metabolites for cytotoxic, the fermentation media play an important role. Carbon sources, nitrogen, salinity, and extracted specimens are important factors in the production of bioactive metabolites for cytotoxic from marine sponge-derived fungi. With this up-to-date review, we attempt to present new minding in the rational discovery of lead compounds for the development of cancer therapy.
Keywords: Marine sponge, fungi, fermentation, cytotoxic, cancer.